Truss optimization / Razif Abu Samah and Hisam Sanip - Abu Samah, Razif; Sanip, Hisam (2001)
The ever-increasing demand on engineers to lower production costs to withstand competition has prompted engineers to look for rigorous methods of decision making, such as optimization methods, to design and produce products both economically and efficiently. Optimization techniques, having reached a degree of maturity over the past several years, are being used in a wide spectrum of industries, including aerospace, automotive, chemical, electrical, and manufacturing industries. With the advent of computer technology and CAD, optimization method are being used to enhance the creative process of conceptual and detailed design of engineering systems. This thesis presents the optimization techniques and applications where emphasize is given to the analysis of truss structures. Although there are many other methods and techniques of engineering optimization, this thesis only uses the techniques of Sequential Unconstrained Optimization, Unconstrained Optimization, and One Dimensional Optimization. These techniques are incorporated in a computer program, which uses the Fortran Compiler. In addition, the Finite Element Method is used to calculate structural analysis. Finally, several case studies mainly in two and three-dimensional truss are conducted to enhance the presentation of the material.